Oligodendroglia Generated From Adult Rat Adipose Tissue by Direct Cell Conversion - Vellosillo, Lara; Pascual-Guerra, Jorge; Muñoz, Maria Paz; Rodríguez-Navarro, José Antonio; González-Nieto, Daniel; Barrio, Luis Carlos; Lobo, Maria del Val Toledo; Paíno, Carlos Luis (Frontiers in Cell and Developmental Biology, 2022)
Obtaining oligodendroglial cells from dispensable tissues would be of great interest for autologous or immunocompatible cell replacement therapy in demyelinating diseases, as well as for studying myelin-related pathologies or testing therapeutic approaches in culture. We evaluated the feasibility of generating oligodendrocyte precursor cells (OPCs) from adult rat adipose tissue by expressing genes encoding transcription factors involved in oligodendroglial development. Adipose-derived mesenchymal cells were lentivirally transduced with tetracycline-inducible Sox10, Olig2, Zfp536, and/or Nkx6.1 transgenes. Immunostaining with the OPC-specific O4 monoclonal antibody was used to mark oligodendroglial induction. O4- and myelin-associated glycoprotein (MAG)-positive cells emerged after 3 weeks when using the Sox10 + Olig2 + Zfp536 combination, followed in the ensuing weeks by GFAP-, O1 antigen-, p75NTR (low-affinity NGF receptor)-, and myelin proteins-positive cells. The O4+ cell population progressively expanded, eventually constituting more than 70 % of cells in culture by 5 months. Sox10 transgene expression was essential for generating O4+ cells but was insufficient for inducing a full oligodendroglial phenotype. Converted cells required continuous transgene expression to maintain their glial phenotype. Some vestigial characteristics of mesenchymal cells were maintained after conversion. Growth factor withdrawal and triiodothyronine (T3) supplementation generated mature oligodendroglial phenotypes, while FBS supplementation produced GFAP+- and p75NTR+-rich cultures. Converted cells also showed functional characteristics of neural-derived OPCs, such as the expression of AMPA, NMDA, kainate, and dopaminergic receptors, as well as similar metabolic responses to differentiation-inducing drugs. When co-cultured with rat dorsal root ganglion neurons, the converted cells differentiated and ensheathed multiple axons. We propose that functional oligodendroglia can be efficiently generated from adult rat mesenchymal cells by direct phenotypic conversion.